JOB ANALYSIS AS A TEACHER RECRUITMENT AND DEVELOPMENT STRATEGY IN ISLAMIC EDUCATION - Wardhani, Suryaningtiyas Puspa; Apriyadi, Ridho; Hadiati, Eti; Junaidah, Junaidah (Universitas Islam Madura, 2025)
Job analysis is a fundamental aspect in the recruitment and development process of teaching staff in Islamic educational institutions. This study aims to identify and analyze effective strategies in the application of job analysis to improve the quality of teacher recruitment and professional development. This study uses a qualitative approach with a case study method. The data was collected through in-depth interviews with principals and teachers at one of the private Islamic schools who have implemented the practice of job analysis systematically. The results of the study show that work analysis carried out in a structured manner is able to provide detailed information about the duties, responsibilities, and competencies required of a teacher. The findings also revealed that clear job descriptions simplify the selection process for prospective teachers and become an important basis for the preparation of training programs and sustainable teacher career development. The conclusion of this study confirms that an integrated job analysis strategy in the human resource management of Islamic education can increase the effectiveness of the recruitment process as well as the quality of teacher development. The practical implications of these findings suggest that Islamic educational institutions need to develop a systematic, institutional needs-based work analysis system as an integral part of educational strategic planning.